Assessing the effectiveness of the patient referral system in remote Zambia: A case study of Mbala District - Austine Dolopo (African Journal of Primary Health Care & Family Medicine, 2026)
Background: Effective patient referral systems are vital for ensuring timely access to advanced healthcare services, particularly in remote areas. In Zambia’s rural districts such as Mbala, the referral system faces critical challenges, including poor road networks, limited ambulance services, unreliable communication infrastructure and a lack of medical personnel at lower-level facilities. These issues contribute to delays, preventable complications, and increased patient morbidity and mortality. Aim: This study aims to assess the effectiveness of the patient referral system in Mbala District by examining logistical, infrastructural and human resource constraints that hinder timely and appropriate patient transfers from rural health facilities to higher-level care. Setting: The study was conducted in Mbala District, a predominantly rural district in Zambia’s Northern province, where geographical barriers, limited health infrastructure, and resource constraints present significant challenges to the effectiveness of the patient referral system. Methods: This study employed a descriptive cross-sectional design. Data were collected over 2 weeks using questionnaires from 18 health facility in-charges and community interviews, then analysed using Jeffreys’s Amazing Statistics Program (JASP) version 0.19.3 to evaluate referral accessibility, timeliness and effectiveness. Results: Statistical analyses show that communication reliability is the strongest predictor of referral success and satisfaction (β = 0.63, p = 0.002), also reducing delays by 1.89 h (β = –1.89, p = 0.007). Distance negatively affects referrals (r = –0.52), with over 70% of facilities beyond 25 km. Grid-powered facilities face 16-h daily power outages. A chi-square test found no significant link between community awareness and satisfaction (χ2 = 1.68, p = 0.1951). Conclusion: The referral system in Mbala District is significantly constrained by logistical and structural barriers. Targeted interventions, including improved transport logistics, communication infrastructure and staff training, are necessary to enhance patient outcomes in rural settings. Contribution: This study contributes empirical evidence on referral barriers in rural Zambia, highlighting communication, transport, distance, infrastructure and staffing as critical determinants of timely and effective patient referrals.